The Lithuanian version of the Zimbardo Time Perspective Inventory (ZTPI) - Liniauskaitė, Audronė; Kairys, Antanas (Psichologija, 2009)
The article presents the process of adaptation of the Zimbardo Time Perspective Inventory (ZPTI) in Lithuania and the psychometric characteristics of the Lithuanian ZTPI version. To assess the construct and its convergent validity, as well as other psychometric characteristics, four studies with the participation of 1529 respondents were conducted. By means of confirmatory factor analysis, the following goodness of fit indices were obtained: Chi-square = 3262.546; df = 1474; p < 0.001; Chi-square/df = 2.216; RMSEA = 0.044; CFI = 0.666; TLI = 0.651. All of them were acceptable, except for the values of CFI and TLI. All the obtained subscale Cronbach alpha values exceeded 0.7, with the exception of Past Positive. The valueof the Past Positive Cronbach‘s alpha coefficient was 0.634. The findings of the study have shown quite acceptable psychometric characteristics of the Lithuanian ZTPI version which does not essentially differ from the original or its adaptations in other countries.
Keywords: time perspective; ZTPI; Lithuanian ZPTI version